Pengaruh Penggunaan Media Audio Visual Berbasis Canva Untuk Meningkatkan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Ekonomi Kelas XI SMAN 1 Mandau - Yasmin, Azura Fataya; Gimin, Gimin; Mujiono (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The research is aimed at finding out the effect of using Canva-based audio visual media to increase students' learning motivation in class XI economics subjects at SMAN 1 Mandau. With the following research, the aim is to determine the differences in students' learning motivation before and after using Canva-based audio visual learning media. This research is quantitative research with experimental methods, and as a measure a Likert scale is used. The sampling technique in this research used a purposive sampling technique, a sampling technique based on class criteria where students' learning motivation was low so that a sample size of 35 respondents was obtained. The data collection technique is by providing a test instrument in the form of a questionnaire. Based on the results of the analysis of different tests on learning motivation questionnaires before and after using Canva-based audio visual media, the questionnaire score before using Canva-based audio visual media was 63.87% and the questionnaire score after using Canva-based audio visual media was 76.79%, and the results of the independent sample t-test The test obtained 11.204 > 1.690, which means there are differences in students' learning motivation before and after using Canva-based audio visual media.